Efektivitas Penggunaan Insulin pada Penderita Diabetes Melitus dengan Kehamilan di Rawat Inap RSD dr. Soebandi Jember Tahun 2012-2013 (Effectivity of Insulin Usage on Diabetic Mellitus Gestational Hospitalized Patient at RSD dr. Soebandi Jember in 2012-20 - Riza Rastri Wihardiyanti; Prihwanto Budi Subagio; Fifteen Aprila Fajrin (Pustaka Kesehatan, 2015)
Gestational diabetes melitus is a diseases that are frequently happen to pregnant women, and is happen to be one of the causes of mortality on mother and fetus. The use of drugs during pregnancy should be prudentially considered for pregnant women, since they are not allowed to consume anti-diabetic drug (OAD) and just allowed to use insulin as therapy. The purpose of this study was to describe the use of insulin, as well as assessing the effectiveness of insulin therapy in patients with gestational diabetes mellitus in RSD dr. Soebandi Jember. The sample in this study was taken from 23 patients. We found that the disease affect 7.69% patients of 20-24 years of age, 11.54% patients of 25-29 years of age, 26.92% patients of 30-34 years of age, 30.77% patients of 35-39 years of age, 7.69% patients of 40-44 years of age and 15.38% patients of above 45 years of age. The insulin used in the sampling is Actrapid for 10 patients and Novorapid for 4 patients. It is known that the effectiveness of insulin based on blood glucose random levels with insulin Actrapid and Novorapid in sub-cutaneous do not have significant differences. Keywords: diabetic mellitus gestational, insulin, antidiabetic drugs